2019
DOI: 10.1002/ange.201906891
|View full text |Cite
|
Sign up to set email alerts
|

Guanitrypmycin Biosynthetic Pathways Imply Cytochrome P450 Mediated Regio‐ and Stereospecific Guaninyl‐Transfer Reactions

Abstract: Mining microbial genomes including those of Streptomyces reveals the presence of al arge number of biosynthetic gene clusters.U nraveling this genetic potential has proved to be au seful approach for novel compound discovery.H ere,wer eport the heterologous expression of two similar P450-associated cyclodipeptide synthase-containing gene clusters in Streptomyces coelicolor and identification of eight rare and novel natural products,t he C3-guaninyl indole alkaloids guanitrypmycins.E xpression of different gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Phylogenetic analysis revealed that EcuN formed an independent branch and was distant from the other cytochrome P450 superfamily proteins from phylogenetically related species (Figure 3A). 47 Along with its close relatives, EcuN also harbors a different amino acid sequence of the functional site of a conserved domain, despite the high identity values from 71.36 to 66.24% (Figure 3B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Phylogenetic analysis revealed that EcuN formed an independent branch and was distant from the other cytochrome P450 superfamily proteins from phylogenetically related species (Figure 3A). 47 Along with its close relatives, EcuN also harbors a different amino acid sequence of the functional site of a conserved domain, despite the high identity values from 71.36 to 66.24% (Figure 3B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Tryptophan is a frequent target of bacterial tailoring enzymes due to its electron-rich indole moiety (Alkhalaf and Ryan 2015 ). Very recently, bacterial P 450 s from several Streptomyces species have been proven to catalyse the linkage of a guanine to a tryptophan residue of CDPs in the biosynthesis of guanitrypmycins and analogues (Liu et al 2019 ; Shi et al 2019 ; Yu et al 2018 ). The elucidation of the biosynthetic pathways was achieved by heterologous expression in Streptomyces coelicolor , precursor feeding experiments and biochemical characterisation with recombinant and purified enzymes.…”
Section: P 450 S As Transferases Of Nucleobases Gumentioning
confidence: 99%
“…Subsequent N-methylation at the guanine residue by GutE leads to the formation of cWY derivative guanitrypmycin A2-1. The BGC from strain B-3589 is also responsible for the formation of the cWF derivative guanitrypmycin A1-1 (Liu et al 2019 ). An almost identical BGC for guanitrypmycin A2-1, termed purincyclamide in that paper, was later identified in Streptomyces chrestomyceticus NA4264, and the corresponding P 450 enzyme was named PcmD (Shi et al 2019 ).…”
Section: P 450 S As Transferases Of Nucleobases Gumentioning
confidence: 99%
“…Several tailoring enzymes found on CDP BGCs, such as oxidases, methyltransferases, prenyltransferases, and 2OG/Fe dioxygenases, also contribute to the core diversification of CDPs. Cytochrome P450s have also been implicated for imparting interesting chemical modifications to CDPs, which include guaninylation, , formation of an intramolecular C–C bond, dimerization, hydroxylation, and oxidation …”
mentioning
confidence: 99%